2017
DOI: 10.1186/s13023-017-0679-0
|View full text |Cite
|
Sign up to set email alerts
|

Inpatient rehabilitation for adult patients with Marfan syndrome: an observational pilot study

Abstract: BackgroundAdvances in medical, interventional and surgical treatment have increased average life expectancy of patients with congenital heart defects. As a result a new group of adult patients with congenital cardiac defects requires medical rehabilitation. Patients with Marfan syndrome (MFS) are a relevant group among these patients. So far, no reports on the effectiveness of specialized rehabilitation programmes for MFS patients exist. We implemented an inpatient 3-week rehabilitation program for MFS patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(73 citation statements)
references
References 29 publications
(33 reference statements)
2
71
0
Order By: Relevance
“…Five studies reported only on patients with MFS according to Ghent 1 nosology. Five studies included only patients assessed according to the revised Ghent nosology (Ghent 2). One study included patients verified Ghents 1 and 2 criteria, and another study included both patients with verified Ghent 1 (n = 13) and patients without verified diagnosis (n = 11).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Five studies reported only on patients with MFS according to Ghent 1 nosology. Five studies included only patients assessed according to the revised Ghent nosology (Ghent 2). One study included patients verified Ghents 1 and 2 criteria, and another study included both patients with verified Ghent 1 (n = 13) and patients without verified diagnosis (n = 11).…”
Section: Resultsmentioning
confidence: 99%
“…All papers used validated, multi‐dimensional scales to measure QoL. Short Form Medical Survey (SF‐36) was used in 10 of the 17 papers dealing with adults and two studies used Short Form Medical survey (SF‐12). Three studies used the Satisfaction with Life Scale (SWLS), one the Ferrans and Power Quality of life Index, cardiac version (QLI, cardiac III), and one used the Ferrans QLI .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations